2004
DOI: 10.1007/s00264-004-0568-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of autograft or allograft in primary anterior cruciate ligament reconstruction

Abstract: Between December 1996 and December 2002, we treated 79 patients with arthroscopy-assisted anterior cruciate ligament (ACL) reconstructions. In 53 patients we used autografts and in 26 patients allografts. Patients were followed up for 38 (12-72) months. The two groups did not differ in preoperative sport activity level. The postoperative Lysholm score was 89.9±8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 21 publications
(24 reference statements)
0
63
0
1
Order By: Relevance
“…Describing the results of primary reconstruction, Barrett et al [3], Kleipool et al [26], Kustos et al [29], and Shelton et al [47] reported no signiWcant diVerence between allografts and autografts with regard to either extension or Xexion. Peterson et al [40] found less pronounced extension deWcits in patients with allografts after 5 years-not, like us, after 2 years.…”
Section: Discussionmentioning
confidence: 98%
“…Describing the results of primary reconstruction, Barrett et al [3], Kleipool et al [26], Kustos et al [29], and Shelton et al [47] reported no signiWcant diVerence between allografts and autografts with regard to either extension or Xexion. Peterson et al [40] found less pronounced extension deWcits in patients with allografts after 5 years-not, like us, after 2 years.…”
Section: Discussionmentioning
confidence: 98%
“…Although many studies in humans do not report different clinical outcomes for the two groups [83,84], several publications have shown an increased knee laxity and rerupture rate after allograft implantation compared with autograft [85]. In vivo studies have shown the remodelling activity of allograft tissue to be delayed with respect to that of autograft, although for both implants, common phases of remodelling were graft necrosis, repopulation and complete substitution (even in autografts) by host cells [86,87].…”
Section: Remodelling Of Allograft Ligament/tendon Tissuesmentioning
confidence: 92%
“…Since then there has been increasing interest in the use of allografts for primary ACL reconstruction, and its role is expanding. There are several published clinical studies (Olson et al, 1992;Pritchard et al, 1995;Siebold et al, 2003;Nyland et al, 2003;Lawhorn and Howell, 2003;Chang et al, 2003;Kustos et al, 2004;Prodromos et al, 2006) evaluating autograft and allograft used in ACL reconstruction, but the findings vary greatly. These discrepancies are due in a large part to the variety of tissues used, and the tremendous variation in surgical technique, fixation, and postoperative protocols.…”
Section: Discussionmentioning
confidence: 99%
“…There are many potential advantages to the use of allograft, including elimination of donor site morbidity, no weakening of the extensor or flexor apparatus, shorter operating time, smaller incisions, less pain, better cosmetic result, easier rehabilitation, lower incidence of postoperative arthrofibrosis, availability of larger grafts, etc., thereby more appropriate for revision surgery, for multiple ligamentous injury or in the presence of patellar baja. Several studies (Siebold et al, 2003;Nyland et al, 2003;Lawhorn and Howell, 2003;Kustos et al, 2004) have shown that allograft is a reasonable alternative to BPTB autograft for ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%